Strategic Benefits, Symbolic Commitments: How Canadian Colleges and Universities Frame Internationalization - Buckner, Elizabeth; Clerk, Scott; Marroquin, Adriana; Zhang, You (Canadian Journal of Higher Education, 2020)
This article examines how Canadian colleges and universities formally articulate their priority activities for internationalization, and what discursive rationales justify their approaches. Data come from 32 publicly-available internationalization strategies published in English by Canadian colleges and universities. In terms of practices, we find that institutions are adopting a largely similar set of activities, focused on partnerships and student and scholarly mobility. In terms of their justifications, we find that most institutions combine the strategic benefits of revenue generation and reputational prestige with symbolic commitments to diversity and excellence. We argue that by drawing on multiple rationales, internationalization strategies imbue the same generic activities with many meanings, which helps the internationalization project garner acceptance from an institution’s diverse stakeholders. In concluding, we also point to a number of noticeably absent ideas, including equity, empathy, humility, and civic responsibility